IRON DEFICIENCY IN EARLY LIFE AND LATER BEHAVIORAL OUTCOMES: A SYSTEMATIC REVIEW - Latifah, Suci; Septiani , Seala; Kusuma, Refani Alycia; Pratiwi, Dessy (Journal of Indonesian Specialized Nutrition, 2025)
Background: Iron deficiency during early life is the most common micronutrient deficiency worldwide and may have lasting effects on neurodevelopment and behavior. This systematic review aimed to explore the relationship between iron deficiency in infancy (0–24 months) and behavioral outcomes beyond two years of age. Methods: This study was a systematic literature review of twenty-three articles. These articles were sourced from scientific journal articles on ScienceDirect, covering studies published between 2005 and 2025. Inclusion criteria were longitudinal cohort or randomized controlled trials assessing behavioral outcomes such as attention, hyperactivity, and socio-emotional regulation. Results: Early-life iron deficiency was consistently associated with increased internalizing and externalizing behaviors, attention deficits, and symptoms of ADHD and Sluggish Cognitive Tempo persisting into adolescence. Timing and severity of deficiency influenced outcomes, with prenatal deficiency affecting recognition memory and executive function, while infant deficiency predicted behavioral dysregulation and academic difficulties. Targeted iron supplementation reduced behavioral problems, whereas excessive or non-individualized supplementation showed limited benefits. Conclusions: Iron deficiency in early life has long-term behavioral consequences. Early detection and individualized interventions are crucial for preventing neurobehavioral impairments and optimizing child development.